Online Dispute Resolution as A Mechanism for Resolving Consumer Disputes in The Marketplace in Seeking Justice - Nabiela Ramadhani; Anita Afriana; Deviana Yuanitasari (Green Publisher Indonesia, 2025)
The rapid growth of e-commerce in Indonesia has increased the volume of marketplace transactions, leading to a surge in consumer disputes. However, current dispute resolution mechanisms remain conventional and ineffective in addressing the unique challenges of digital transactions. This study aims to analyze the implementation of Online Dispute Resolution (ODR) as an alternative mechanism for resolving consumer disputes in marketplace transactions, and to examine the urgency of establishing a comprehensive legal framework for ODR in Indonesia. Employing a normative juridical approach, this research reviews primary and secondary legal materials, including laws, regulations, and relevant literature, with qualitative descriptive analysis. The findings reveal that Indonesia lacks specific ODR regulations, limiting its optimal application despite its recognition in existing laws. Implementing ODR can enhance consumer access to justice by providing faster, simpler, cost-effective dispute resolution methods. The study emphasizes the need for comprehensive legal reforms to regulate ODR procedures, institutional responsibilities, data security, and the enforceability of ODR decisions. Strengthening the legal basis for ODR will improve consumer protection, legal certainty, and public trust in digital transactions, supporting a fairer digital economy.